Electrocardiogram signal generation using electrical model of cardiac cell: application in cardiac ischemia. (19th May 2019) - Fallahi, Alireza; Khorram, Hamidreza Ghanbari; Kokabi, Alireza
Abstract: One of the most common causes of heart failure is ischaemia. In this disease, the heart muscles die due to the lack or insufficiency of the blood in the cardiac veins. As a result of such a phenomenon, the action potential in that part of the heart would fade. In this article, using the electric model of the cardiac cell and the mechanism of producing an ECG signal in the heart, the process of producing cardiac electrical potential has been modelled. In this regard, the basic constituent signals of the ECG are generated. Afterward, by accumulating these signals, the final ECG is reproduced. In addition, by variation of the presented model parameters, the cardiac ischaemic signal is simulated in a way that the influence of ventricle ischaemia on the ventricular tissues is considered. The results of such a simulation demonstrate a sufficient match between the model output and the reported changes of the cardiac arrhythmia including ischaemic failures. Here, we report the 91% match between the simulated signal and the considered clinical data.